Relation of clinical, serological, morphological, and electrophysiological findings in galactocerebroside-induced experimental allergic neuritis. Issue 3 (March 1986) - Stoll, G; Schwendemann, G; Heininger, K; Köhne, W; Hartung, H P; Seitz, R; Toyka, K V
Abstract : Rabbits were immunised repeatedly with bovine brain galactocerebroside. Almost all animals developed overt polyradiculoneuropathy. Circulating IgG antibodies to galactocerebroside in the serum and deposits of IgG in the spinal roots were detectable weeks before definite clinical, morphological, and electrophysiological alterations occurred. The levels of IgG antibody titres to galactocerebroside did not correlate with the severity of the clinical disease and of nerve conduction slowing. Remyelination and a virtually complete recovery of nerve dysfunction occurred although circulating antibodies to galactocerebroside were still present.